Reduction of Glucocorticoid Receptor Function in Chronic Fatigue Syndrome. (10th June 2018) - Lynn, Megan; Maclachlan, Laura; Finkelmeyer, Andreas; Clark, James; Locke, James; Todryk, Stephen; Ng, Wan-Fai; Newton, Julia L.; Watson, Stuart
Abstract : Glucocorticoid receptor (GR) function may have aetiopathogenic significance in chronic fatigue syndrome (CFS), via its essential role in mediating inflammatory responses as well as in hypothalamic-pituitary-adrenal axis regulation. GR function can be estimated ex vivo by measuring dexamethasone (dex) modulation of cytokine response to lipopolysaccharide (LPS), and in vivo using the impact of dex on cortisol levels. This study aimed to compare the GR function between CFS (n = 48 ), primary Sjögren's syndrome (a disease group control) (n = 27 ), and sedentary healthy controls (HCs) (n = 20 ), and to investigate its relationship with clinical measures. In the GR ex vivo response assay, whole blood was diluted and incubated with LPS (to stimulate cytokine production), with or without 10 or 100 nanomolar concentrations of dex. Cytometric bead array (CBA) and flow cytometry enabled quantification of cytokine levels (TNF α, interleukin- (IL-) 6, and IL-10) in the supernatants. In the in vivo response assay, five plasma samples were taken for determination of total cortisol concentration using ELISA at half-hourly intervals on two consecutive mornings separated by ingestion of 0.5 mg of dex at 11 pm. The association of the data from the in vivo and ex vivo analyses with reported childhood adversity was also examined. CFS patients had reduced LPS-induced IL-6 and TNF α production compared to both control groups and reduced suppression of TNF α by the higher dose of dex compared to HCs. Cortisol levels, before or after dex, did not differ between CFS and HCs. Cortisol levels were more variable in CFS than HCs. In the combined group (CFS plus HC), cortisol concentrations positively and ex vivo GR function (determined by dex-mediated suppression of IL-10) negatively correlated with childhood adversity score. The results do not support the hypothesis that GR dysregulation is aetiopathogenic in CFS and suggest that current and future endocrine cross-sectional studies in CFS may be vulnerable to the confounding influence of childhood trauma which is likely increased by comorbid depression.